Related Function:

The FISHERINV function returns the inverse of the Fisher transformation, i.e. if y = \text{FISHER}(x), then \text{FISHERINV}(y) = x.

Syntax

=FISHERINV(y)

Arguments

Argument Description
y The value for which you want to perform the inverse of the transformation

Examples

  A B C
1 Formula Result Notes
2 =FISHERINV(0.8) 0.664037 Inverse of the Fisher transformation at 0.8
3 =FISHERINV(-0.25) -0.24492 Inverse of the Fisher transformation at -0.25
4 =FISHERINV(2.5) 0.986614 Inverse of the Fisher transformation at 2.5

Common Function Error(s)

Problem What went wrong
#VALUE! Occurs if the supplied value of y is not recognized as a numeric value

The equation for the Fisher transformation is:    

    \[    z' = \frac 1{2} \ln \left( \frac{1+x}{1-x} \right)    \]

The equation for the inverse Fisher transformation is:

    \[    x = \frac {e^{2y} - 1}{e^{2y} + 1}    \]

See Wikipedia for more information on Fisher Transformation.